The Effect of Job Stress on Employee Performance at the Office of the Ministry of Religion of Polewali Mandar Regency - Kabbani, Muh. Abraar; Kurniawan, Agung Widhi; Musa, Chalid Imran (Entrepreneurship, Management, and Business Research Journal, 2024)
Penelitian ini bertujuan untuk mengetahui pengaruh stres kerja terhadap kinerja pegawai pada Kementerian Agama Kabupaten Polewali Mandar. Variabel Penelitian ini terdiri dari stres kerja dan kinerja pegawai. Jenis penelitian ini adalah kuantitatif bersifat asosiatif. Adapun populasi dalam penelitian ini berjumlah 219 orang pegawai kantor Kementerian Agama Kabupaten Polewali Mandar. Teknik pengambilan sampel yang digunakan ialah rumus Slovin dengan jumlah sampel sebanyak 69 responden yaitu keseluruhan populasi. Teknik pengumpulan data dilakukan dengan penyebaran kuesioner kepada pegawai. Teknik analisis data menggunakan regresi sederhana dengan bantuan software SPSS versi 25. Hasil penelitian ini menunjukkan bahwa stress kerja memberikan pengaruh positif dan signifikan secara parsial pada kinerja pegawai kantor Kementerian Agama Kabupaten Polewali Mandar. This research then found that work motivation from employees, both intrinsic and extrinsic, has an important role in improving employee performance, in other words, work motivation has a positive and significant effect on the performance of MSME employees. This study aims to determine the effect of work stress on employee performance at the Ministry of Religion of Polewali Mandar Regency. This research variable consists of job stress and employee performance. This type of research is quantitative associative. The population in this study amounted to 219 employees of the Ministry of Religion of Polewali Mandar Regency. The sampling technique used was the Slovin formula with a sample size of 69 respondents, namely the entire population. The data collection technique was carried out by distributing questionnaires to employees. Data analysis techniques using simple regression with the help of SPSS software version 25. The results of this study indicate that work stress has a positive and significant effect partially on the performance of employees of the Polewali Mandar Regency Ministry of Religion office.